Faktor-Faktor Penyebab Agresivitas Pada Anak Usia Dini di “X” Islamic Preschool Yogyakarta - Faisal Akbar; Alif Mualifah; Purwadi (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2021)
This study aims to determine in-depth the factors that cause aggressiveness in early childhood at “X Islamic Preschool Yogyakarta. Subjects in this study amounted to 3 early childhood (AUD) who studied at “X” Islamic Preschool. Two are male and one is female. The three children did not have a history of attention deficit and hyperactive disorder (ADHD). Significant persons in this study are parents (father and mother), teachers, and also household assistants (especially for subjects who have it). The method used in this research is qualitative with a collective case study approach. Data collection techniques by interview, observation, and documentation. The data obtained were analyzed using a content analysis approach. The result revealed the factors causing aggressiveness are untrained emotional skills. In addition, there are also new findings in this study, namely: unfulfilled desires and parenting tend to be permissive. The new findings in this study can complement studies related to aggressive behavior, especially in early childhood.